Lipid Droplets: A Significant but Understudied Contributor of Host–Bacterial Interactions - Libbing, Cassandra L. (Cells, 2019)
Lipid droplets (LDs) are cytosolic lipid storage organelles that are important for cellular lipid metabolism, energy homeostasis, cell signaling, and inflammation. Several bacterial, viral and protozoal pathogens exploit host LDs to promote infection, thus emphasizing the importance of LDs at the host–pathogen interface. In this review, we discuss the thus far reported relation between host LDs and bacterial pathogens including obligate and facultative intracellular bacteria, and extracellular bacteria. Although there is less evidence for a LD–extracellular bacterial interaction compared to interactions with intracellular bacteria, in this review, we attempt to compare the bacterial mechanisms that target LDs, the host signaling pathways involved and the utilization of LDs by these bacteria. Many intracellular bacteria employ unique mechanisms to target host LDs and potentially obtain nutrients and lipids for vacuolar biogenesis and/or immune evasion. However, extracellular bacteria utilize LDs to either promote host tissue damage or induce host death. We also identify several areas that require further investigation. Along with identifying LD interactions with bacteria besides the ones reported, the precise mechanisms of LD targeting and how LDs benefit pathogens should be explored for the bacteria discussed in the review. Elucidating LD–bacterial interactions promises critical insight into a novel host–pathogen interaction.